Icarus' second chance the basis and perspectives of space ethics - Arnould, Jacques (Studies in space policy, 2011)
2011: fifty years separate us from the flight of Yuri Gagarin. Fifty years of extraordinary successes, with the kind of apotheosis represented by the first man on the moon; fifty years also of bitter failures, even tragic when they involved the deaths of human beings; finally, fifty years during which space largely contributed to the scientific and technical, political and economic, cultural and social transformation of humanity. This is a critical analysis of the decisions and the actions which constituted and constitute still the field of astronautic activities, to analyse this field's strategies and choices, their consequences on the natural environment and on humans, in short to work out and apply an ethical investigation. This work is the fruit of research carried out by the French Centre National d'Etudes Spatiales (CNES) over the past ten years, in collaboration with many organisations, astronautical or not: ESA, NASA and especially ESPI.